Responsible lobbying: an empirical study in the EU. Issue 1 (3rd May 2016) - Bauer, Theresa
Abstract : Purpose: The purpose of this paper is to explore the awareness and practice responsible lobbying in the EU. Specifically, the purpose of this paper is to examine the extent to which responsible lobbying criteria are fulfilled and to investigate whether responsible lobbying yields concrete benefits in the political arena. Design/methodology/approach: The study takes a quantitative approach combining descriptive and multivariate partial least squares (PLS) analysis based on data gained from an online survey among lobbyists in the EU. A new measurement instrument for responsible lobbying is used that grasps the multidimensional phenomenon with a formative-formative higher-order construct. Findings: The study reveals that criteria of responsible lobbying are fulfilled to a large extent according to the lobbyists. The PLS analysis confirms the applicability of the multidimensional model of responsible lobbying, although there is only a weak link between Dimension (1), referring to the company's stated corporate social responsibility (CSR) commitment and coherence with lobbying and the second-order construct responsible lobbying. Based on the information given by respondents, the analysis provides evidence for a positive impact of responsible lobbying on both lobbying success and corporate reputation, but also for the dependence of these two variables on additional factors. Originality/value: Responsible lobbying as an aligned approach to CSR and lobbying is a long neglected research topic, which has been gaining interest recently. This study contributes to empirical knowledge on the awareness and practice of responsible lobbying in the EU by taking a quantitative approach based on a solid theoretical foundation.